Level of Competitiveness Building of Farm Women in Assam through Extension Services - Saikia, Poree; Das, Manju Dutta; Deka, Manoshi Baruahava (International Journal of Bio-resource and Stress Management, 2016)
Women plays a significant and crucial role in agricultural development and allied fields including in the main crop production, livestock production, horticulture, post-harvest operations, fisheries etc., the nature and extent of women’s involvement in agriculture, no doubt, varies greatly from region to region. But despite their importance to agricultural production, women face severe handicaps. Agricultural development programmers are usually planned by men and aimed at men. All agricultural services still have a sex bias in favors of men. Women are generally by-passed in development efforts. They are in urgent need of understanding and acquiring new knowledge and skills on cultivation of crops, so that they could contribute more effectively to the production process. Thus the important contribution made by women of Assam in agriculture, provides the necessary basis and justification for the present research study. The study was conducted in three agro-climatic zones of Assam. A multistage purposive cum random sampling design was followed. Altogether 1200 farm women were included as sample of respondents. Data were collected with the help of structured interview schedule and questionnaire. 52.60% of farm women belonged to low socio-economic status. 51.92% of farm women had medium level of achievement motivation. Majority (54.75%) of farm women had medium level of economic motivation. Majority (55.17%) of farm women had medium level of innovation proneness. 48.25% of farm women had medium level of self-confident. 49.33% of farm women had medium level of risk bearing ability.